Technology Transfer Contracts - Ahmed Hameed Karim (International Journal of Law Research and Studies, 2026)
Technology has become an active player at the international level, as it has become the lifeblood of life in all its aspects. Therefore, technology needs a legal framework that regulates the relationship between the parties involved in the manufacture and production of this technology, those who possess it, and those who transfer it. As with any new legal system, disputes arise, because they relate to technical and technological interests. Therefore, the question arises about the mechanism for resolving these disputes. The nature of these contracts is always linked to countries, since technology cannot be confined to a narrow scope or to the territory of one country only. Therefore, political considerations enter into this type of contract, and their impact is particularly evident in the mechanisms for settling disputes in technology transfer contracts.